IMPROVING WRITING SKILL THROUGH READING MATERIALS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
How to increase level of writing through reading pessages. In this article some structures are mentioned that can help to improve writing skills.